Strategi Komunikasi Pemasaran Pesantren Syekh Muhammad Baqi Babussalam Basilam Baru dalam Meningkatkan Minat Santri Barudibatang Angkola, Tapanuli Selatan - Salsah Fadilah Siregar; Abdul Rasyid (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is entitled "Marketing strategy for the Syekh Muhammad Baqi Babussalam Basilam Baru Islamic Boarding School in attracting the interest of new students in Angkola South Tapanuli. The following is a paraphrase of the text provided. This research was conducted on Jl. Mandailing Km.11.5 Basilam Baru Village, Batang Angkola District, South Tapanuli using a qualitative approach. The subjects of this research include the Board of Teachers/Islamic Boarding School Management, Publication Division, and Social Media Marketing. The information gathering techniques used are perception and meetings. In this exploration, the researchers utilized source triangulation by checking and confirming with the Islamic Live-in School Sheikh Muhammad Baqi Babussalam Basilam Baru regarding the promotion of correspondence methodology information carried out by the Islamic Life Experience School. The research results show that the publication techniques carried out by the Live-in Islamic School of Syekh Muhammad Baqi Babussalam Basilam Baru include print media and virtual entertainment, with print media as handouts. In the individual sales technique, the supervisory team does not form a committed marketing group or provide the power to track new clients; Secret deals are concluded during competition events. Techniques for increasing transactions carried out by Islamic Life Experience Schools include rebate programs for homeless people who are not bothered by food costs, free teaching programs, and organizing events. For Advertising activities for the All Inclusive Islamic School of Sheikh Muhammad Baqi Babussalam Basilam Baru.